2015
DOI: 10.1007/s10266-015-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of FDG-PET to detect a chronic odontogenic infection as a possible source of the brain abscess

Abstract: This study describes the use of (18)F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET) to detect a chronic odontogenic infection as the possible origin of a brain abscess (BA). A 74-year-old man with esophageal carcinoma was referred to our department to determine the origin of a BA in his oral cavity. He had no acute odontogenic infections. The BA was drained, and bacteria of the Staphylococcus milleri group were detected. Whole body FDG-PET revealed that the only sites of definite uptake of FDG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Although not specific to actinomycosis, imaging can show abnormalities such as cerebral and/or orbital abscess, meningitis and subdural/epidural empyema [4]. Interestingly, Sato et al recently described FDG-PET scan findings identifying an odontogenic infection as the cause of a brain abscess [24] Unfortunately, in our case no such findings were seen on the FDG-PET scan. Actinomycetes are extremely difficult to culture [5, 25].…”
Section: Discussionmentioning
confidence: 70%
“…Although not specific to actinomycosis, imaging can show abnormalities such as cerebral and/or orbital abscess, meningitis and subdural/epidural empyema [4]. Interestingly, Sato et al recently described FDG-PET scan findings identifying an odontogenic infection as the cause of a brain abscess [24] Unfortunately, in our case no such findings were seen on the FDG-PET scan. Actinomycetes are extremely difficult to culture [5, 25].…”
Section: Discussionmentioning
confidence: 70%
“…Oral periodontal abscess is an oral infective, painful disease that can spread (Yoneda et al, 2011; Herrera et al, 2014; Sato et al, 2016), and it is a valuable potential sign of undiagnosed type 2 diabetes (Alagl, 2017). Several studies have identified the dominant microbiota by culture-based diagnostic methods (Newman and Sims, 1979; Jaramillo et al, 2005; Xie et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MR spectroscopy detects the products of bacterial metabolism (lactate, acetate, and succinate) and neutrophil proteolysis (cytosolic amino acids), which are used as support. It has even been reported that the combined use of DWI and MR spectroscopy increased the specificity and sensitivity to 95.2% and 100%, respectively [5 , 6] .…”
Section: Discussionmentioning
confidence: 99%
“…Abscess evacuation surgery without proper antibiotic coverage is less meaningful in handling. Brain abscesses are generally treated with antimicrobial therapy for a minimum of 4-8 weeks but longer for abscesses treated with medical therapy without surgical excision [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . In this case, the patient experienced successful 28 weeks of adequate antibiotic therapy as seen on a contrast-enhanced head MRI showing resolution of the abscess diameter and clinical improvement of vertigo in the patient.…”
Section: Discussionmentioning
confidence: 99%